SOCIAL CRITICISM OF THE LOWER CLASS IN THE NOVEL PURWACINTRAKA BY TULUS SETIYADI: KRITIK SOSIAL MASYARAKAT KELAS BAWAH DALAM NOVEL PURWACINTRAKA KARYA TULUS SETIYADI - Nela Mega Anjar Sari; Widodo Widodo (LLDIKTI Wilayah X, 2024)
The lower-class society (wong cilik) consists of impoverished individuals struggling to meet their daily needs. This group often faces mistreatment due to social structures. This study aims to identify the types of social criticism of the lower-class society, specifically poverty, low morals, and injustice in the novel Purwacintraka. This research employed a qualitative descriptive method. The theory used is Alan Swingewood's sociology of literature theory, utilizing reading and note-taking techniques. The data consisted of text from the novel Purwacintraka by Tulus Setiyadi. Miles & Huberman's model of analysis was used to explore social criticism within the text. The research results indicated that social criticism encompasses poverty, low morals, and injustice. These criticisms were depicted through social issues reflected in the novel Purwacintraka, such as inadequate housing, difficulty in meeting food and educational expenses. Poverty also leads to moral decline, resulting in negative actions such as gambling and prostitution. The injustice described involved the upper-class society oppressing and discriminating against the lower-class society due to social structures. This research served as a means of critique to raise awareness of the social inequality experienced by the lower-class society as depicted in the novel.